2008
DOI: 10.1007/s10493-008-9183-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of leaf trichomes on predatory mite (Typhlodromus pyri) abundance in grape varieties

Abstract: Non-glandular leaf trichomes positively inXuence the abundance of many phytoseiid mites. We characterized the inXuence of grape leaf trichomes (domatia, hairs, and bristles) on Typhlodromus pyri Scheuten abundance over two years in a common garden planting of many grape varieties and 2 years of sampling in a commercial vineyard. In general, a lack of trichomes was associated with much lower predator numbers and in the case of Dechaunac, a cultivar with almost no trichomes, very few T. pyri were found. Phytosei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 36 publications
5
40
1
6
Order By: Relevance
“…Segundo Duso e Vettorazzo (1999), os fitoseídeos Kampimodromus aberrans (Oudemans) e Typhlodromus pyri Scheuten estão mais adaptados às cultivares pilosas, e Amblyseius andersoni (Chant), às cultivares glabras. Nesse sentido, estudos realizados com 12 cultivares de videira, nos Estados Unidos da América, identificaram uma correlação forte entre a sobrevivência no vinhedo de T. pyri e a densidade de tricomas não glandulares nas folhas (LOUGHNER et al, 2008).…”
Section: Resultados E Discussão Ano Agrícola De 2005/2006unclassified
“…Segundo Duso e Vettorazzo (1999), os fitoseídeos Kampimodromus aberrans (Oudemans) e Typhlodromus pyri Scheuten estão mais adaptados às cultivares pilosas, e Amblyseius andersoni (Chant), às cultivares glabras. Nesse sentido, estudos realizados com 12 cultivares de videira, nos Estados Unidos da América, identificaram uma correlação forte entre a sobrevivência no vinhedo de T. pyri e a densidade de tricomas não glandulares nas folhas (LOUGHNER et al, 2008).…”
Section: Resultados E Discussão Ano Agrícola De 2005/2006unclassified
“…The number of trichomes have no obvious impacts on the total fecundity. However, Loughner (2008) reported that a lack of trichomes was associated with much lower predator numbers. The fecundity is an important factor that effects on the number of arthropod (Loughner et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Trichomes on the surfaces of aerial parts of plants are distributed like biological antenna exposed to a variety of environmental cues (Roy et al, 1999;Wagner, 1991) and serve as the first procession for plants to encounter multiple extrinsic challenges (Amme et al, 2005;Loughner et al, 2008). Growing at the most external parts of plants, leaf trichomes are assumed to function as a channel to connect the extrinsic signals with intrinsic plant signalling pathways (Amme et al, 2005;Kanzaki et al, 2008;Roy et al, 1999;Traw and Bergelson, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, trichomes interfere with the feeding of herbivores (Esau, 1965) and constitute physical defensive structures, which sometimes simply have the potential to impede infestation of insect pests (Ambrósio et al, 2008). Alternatively, plant protection can be provided by natural enemies of insects that impose selection for increased trichome density (Loughner et al, 2008). Evidence also shows the influence of leaf trichomes on foliar fungal infection; to prevent these infections, trichomes are particularly important because they secrete compounds that have antimicrobial activities and contribute to plant defence against pathogens (Amme et al, 2005;Calo et al, 2006;Skaltsa et al, 1994).…”
Section: Introductionmentioning
confidence: 99%